ANALISIS KINERJA KEUANGAN PT. ASTRA INTERNASIONAL TBK. DENGAN ALAT UKUR MVA (MARKET VALUE ADDED) - CITRA AGUSTIN, INDI Citra (Jurnal Akuntansi AKUNESA, 2014)
This research analyse the financial performance of PT. Astra Internasional Tbk. with using Market Value Added (MVA). This research using case study. The data of this research using annual report of PT. Astra Internasional Tbk. in period 2009-2013. Based on the calculation result value of MVA that show positive numbers in period 2009-2013, it means that management has been able to give prosperity for shareholder in that period. But the value of MVA in period 2012-2013 show an decrease compare to the value of MVA in period 2011. This value’s decrease because of stock price of that year which also show an decrease than before year. Another reason PT. Astra Internasional Tbk. in every year always show an increase on value of invested capital’s firm, so management has an decrease to maximum the capital gain of shareholder in period 2012-2013.Keywords: Stock, Analyse the financial performance, MVA